Thermophysical properties for (diethyl carbonate +p-xylene + octane) ternary system - Mosteiro, L. (2011)
The density and speed of sound of the ternary mixture (diethyl carbonate + p-xylene + octane) have been measured at atmospheric pressure and in the temperature range T = (288.15 to 308.15) K. Besides, surface tension has been also determined for the same mixture at T = 298.15 K. The experimental measurements have allowed the calculation of the corresponding derived properties: excess molar volumes, excess isentropic compressibilities, and surface tension deviations. Excess properties have been correlated using Nagata and Tamura equation and correlation for the surface tension deviation has been done with the Cibulka equation. Good accuracy has been obtained. Based on the variations of the derived properties values with composition, a qualitative discussion about the intermolecular interactions was drawn.